Senolytic and mitogenic activities of Moringa oleifera Lam. leaf extract on culture expanded and doxorubicin oxidative stress-induced umbilical cord mesenchymal stem cells - Adamu, Muhammad Umar (2022)
Mesenchymal stem cells are potent tools in tissue engineering, regenerative medicine, and drug discovery. The ex-vivo expansion of MSCs has become necessary to harvest a desirable number of cells for research or clinical use. However, the ex-vivo expansion of MSCs remains a challenge due to decreased cell proliferation due to cellular senescence. Several approaches to mitigate such effects abound, including hypoxia cell culture environment, modification of cell culture surfaces, and the use of small molecules. The use of small molecules is promising because of convenience, cost, and broad applicability compared to other approaches. Interestingly, polyphenols such as quercetin and astragalin are the leading small molecule candidates with senolytic and mitogenic activities that promote laboratory-based cell propagation. Hence, the objective of this study was to evaluate the activity of Moringa oleifera leaves ethanolic extract (MOEE), enriched with polyphenols, on proliferation and antisenescence of MSCs. Moringa oleifera ethanolic leaves extract (MOEE) was subjected to UHPLC/MS and HPLC to identify and quantify constituent polyphenolic compounds. Next, UC-MSCs were generated by explant method and characterized by immunophenotyping and mesodermal differentiation assays. UC-MSCs were subjected to serial passaging and in parallel treated with DOX to induced oxidative stress and, thereafter treated with MOEE for 48 h and 72 h respectively to examine its effects on proliferation, reactive oxygen species generation, apoptosis, stemness, replicative stress and oxidative stress induced senescence as well as gene expressional changes. Cytotoxicity of MOEE was measured by MTT assay while proliferation was assessed by DNA content analysis, cell cycle analysis, and population growth kinetics. Apoptosis assay was measured by annexin-V/PI assay, reactive oxygen species generation (ROS) by 2'7' dichlorofluorescin diacetate (DCFH-DA) assay, stemness was measured by immunophenotyping of hMSCs surface markers, followed by cellular senescence evaluated by -galactosidase staining and C12FDG assay, while senescence-associated secretory phenotype was gauged by cytokine bead array (CBA) test. Gene expression of NRF2 and FOXO3a was evaluated by RT-qPCR. Eight polyphenols were identified by UHPLC/MS among which astragalin and quercetin were quantified by HPLC. Supplementation with graded concentration of MOEE (100, 10, 1, 0.1 g/mL) for 48 hours profoundly improved the proliferation and viability of culture expanded late passaged UC-MSCs (P7-P10) compared to early passage MSCs (P3-P6) with an IC50 of 840 g/mL. These findings were corroborated with a decrease in culture-induced early apoptotic cells in the late passage UC-MSCs and increased S-phase cells of the cell cycle. Further, it improves the population growth kinetics in the late passage UC-MSCs, maintain their stemness, and enhances their osteogenic differentiation via increase expression of CD73 surface marker. MOEE also decrease the release of interleukin 6, however it does not retard the accumulation of senescent cells in culture expanded late passaged UC-MSCs. In doxorubicin induced oxidative stress senescence model, administration of MOEE (100, 10, 1, 0.1 g/mL) for 72 hours improves viability of UC-MSCs in the oxidative stress microenvironment through the scavenging of reactive oxygen species. Similarly, MOEE mitigated cell cycle arrest by enhancing their re-entry to the S-Phase of the cell cycle and prevent apoptosis induced by ROS accumulation. Interestingly, MOEE blocks senescence development in oxidative stress environment (decrease - galactosidase expression and decrease percentage of senescent cells) as well as the secretion of senescence-associated secretory phenotype: IL-1, IL-6 and IL-8— known to spread senescence to neighbouring healthy cells. Gene expression studies implicate the involvement of FOXO3a, an antiaging and antioxidant transcription factor, and NRF2, a master regulator of the antioxidant gene as the possible transcriptional factors upregulated by MOEE to exerts its effects in the oxidative stress milieu. MOEE administration in standard laboratory conditions promotes the proliferation and viability of late passage UC-MSCs, prevents culture-induced apoptosis, and enhances the osteogenic differentiation ability of MSCs. Furthermore, when UC-MSCs are challenged with oxidative stress, MOEE prevents the senescence and apoptosis of MSCs, promotes their entry to the cell cycle, and improves the expression of transcriptional factors that enhance the antioxidative and antisenescence status of UCMSCs. The laboratory investigation has explored the potential use of MOEE in propagating UC-MSCs; hence it can be further evaluated in GMP conditions to assure safe clinical-scale manufacturing. However, it is vital to ascertain the safe use of MOEE through genetic screening and animal model-based evaluation to conclude their mitogenic and senolytic activities.